Elementos do ritmo lento da territorialização do agroartesanato familiar em Francisco Beltrão/PR - Eduardo, Márcio Freitas [UNESP]; Saquet, Marcos Aurelio (My University, 2010)
In this paper, we reveal some results of our research over the dynamic of territorial units family production that produce food through processing techniques and technologies rudimentary and family work in the municipality of Francisco Beltrão (PR). This production process results from a specific historical and territorial, marked by the colonization held in the Southwestern part of Paraná by German, Pole and italian descendants from Rio Grande do Sul and Santa Catarina. They reproduce knowledge and experiences that shape a heritage of this territory through the production agroworkmanship. This is continued, in many situations, even in the face of advancing forces and agents of capital in agrarian space, featuring overlapping and complementary territorialities.
Elements of the slow rhythm of the territorial action of the craft rural and familiar industry in Francisco Beltrão/PR
Keywords: Development; Pace; Territory